2020
DOI: 10.15585/mmwr.mm6928e3
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Cloth Face Covering Use Among Adults During the COVID-19 Pandemic — United States, April and May 2020

Abstract: On July 14, 2020, this report was posted as an MMWR Early Release on the MMWR website (https://www.cdc.gov/mmwr). On April 3, 2020, the White House Coronavirus Task Force and CDC announced a new behavioral recommendation to help slow the spread of coronavirus disease 2019 (COVID-19) by encouraging the use of a cloth face covering when out in public (1). Widespread use of cloth face coverings has not been studied among the U.S. population, and therefore, little is known about encouraging the public to adopt thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
103
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(116 citation statements)
references
References 6 publications
9
103
1
3
Order By: Relevance
“…During this pandemic, higher perceived risk has been associated with increased handwashing (6). In addition to hand hygiene, risk perceptions have been associated with engaging in other protective behaviors such as physical distancing, § § § avoiding handshakes and crowds 7, and wearing cloth face masks (8). Perceived risk for COVID-19 in the United States, when assessed during March-April 2020, was moderately high (6); however, some evidence indicates U.S. adults underestimate their risk of becoming ill with COVID-19 (7).…”
Section: Discussionmentioning
confidence: 99%
“…During this pandemic, higher perceived risk has been associated with increased handwashing (6). In addition to hand hygiene, risk perceptions have been associated with engaging in other protective behaviors such as physical distancing, § § § avoiding handshakes and crowds 7, and wearing cloth face masks (8). Perceived risk for COVID-19 in the United States, when assessed during March-April 2020, was moderately high (6); however, some evidence indicates U.S. adults underestimate their risk of becoming ill with COVID-19 (7).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the disparity between Black and White individuals in testing positive slightly decreased over the study period and was highest at VA sites that experienced an early outbreak of COVID-19. This finding may be partially explained by the increased attention on racial disparities in COVID-19 in the media [3][4][5] that may have impacted behaviors like wearing face coverings in public to reduce the spread of infection [38].…”
Section: Findings In Contextmentioning
confidence: 99%
“…A recent survey found that persons aged 18-24 years reported lower agreement with and adherence to public health guidance (e.g., wearing masks) compared with those aged ≥25 years (2). Identifying factors (e.g., perceived severity of disease outcome) that influence risk for exposure to COVID-19 and framing communication messages to target those factors might persuade young adults to engage in behaviors that are effective in preventing the spread of COVID-19 (6,7).…”
mentioning
confidence: 99%